Analysis of the Effect of Working Hours, Type of Vehicle, Age, and Education on Income for Formal and Informal Workers - Vebrina Hania Cholily (Jurnal Indonesia Sosial Sains, 2022)
The factors that influence the income of motorcycle taxi drivers in the formal and informal sectors are age, education level, working hours, and the type of vehicle used. This study aims to determine the factors that influence the income of motorcycle taxi workers in the formal sector and informal sector, and the influence of age, education, working hours, and type of vehicle. on the income level of taxi drivers in the formal and informal sectors. This case study research was conducted in Semarang City. The method used in this study is primary data with quantitative methods. Data collection techniques through direct interviews with respondents. The samples taken were 80 respondents using the Simple Random Sampling technique. Based on the results of the study, it was stated that the variables of age and working hours had an effect on the income of conventional motorcycle taxi drivers and motorcycle taxi drivers in the city of Semarang. The education variable has an effect on the income earned by formal workers, but not so much for informal workers. On the other hand, the type of vehicle has a significant effect on the income of informal workers but has no effect on formal workers.